Can an Augmented Reality Headset Improve Accuracy of Acetabular Cup Orientation in Simulated THA? A Randomized Trial. - Logishetty,K; Western,L; Morgan,R; Iranpour,F; Cobb,JP; Auvinet,E (Clin Orthop Relat Res, 2018)
BACKGROUND: Accurate implant orientation reduces wear and increases stability in arthroplasty but is a technically demanding skill. Augmented reality (AR) headsets overlay digital information on top of the real world. We have developed an enhanced AR headset capable of tracking bony anatomy in relation to an implant, but it has not yet been assessed for its suitability as a training tool for implant orientation. QUESTIONS/PURPOSES: (1) In the setting of simulated THA performed by novices, does an AR headset improve the accuracy of acetabular component positioning compared with hands-on training by an expert surgeon? (2) What are trainees' perceptions of the AR headset in terms of realism of the task, acceptability of the technology, and its potential role for surgical training? METHODS: Twenty-four study participants (medical students in their final year of school, who were applying to surgery residency programs, and who had no prior arthroplasty experience) participated in a randomized simulation trial using an AR headset and a simulated THA. Participants were randomized to two groups completing four once-weekly sessions of baseline assessment, training, and reassessment. One group trained using AR (with live holographic orientation feedback) and the other received one-on-one training from a hip arthroplasty surgeon. Demographics and baseline performance in orienting an acetabular implant to six patient-specific values on the phantom pelvis were collected before training and were comparable. The orientation error in degrees between the planned and achieved orientations was measured and was not different between groups with the numbers available (surgeon group mean error ± SD 16° ± 7° versus AR 14° ± 7°; p = 0.22). Participants trained by AR also completed a validated posttraining questionnaire evaluating their experiences. RESULTS: During the four training sessions, participants using AR-guidance had smaller mean (± SD) e